Efektivitas Fungsi Manajerial Kepala Sekolah Terhadap Kinerja Guru - Andi Maryam; Ira Irviana (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study is a qualitative research that aims to examine the effectiveness of the principals’ managerial functions on teachers’ performance of the Cluster III in Makassar Subdistrict of Makassar City. The independent variable of the study was the principals’ managerial functions, while the dependent variable was the teachers’ performance. The population of the study was the Elementary School of Cluster III in Makassar Subdistrict of Makassar City. The samples were the principals and homeroom teachers of grade V with a total of five principals and five homeroom teachers. The data of the study were obtained through interview, observation, and documentation. Based on the results of the study, it can be concluded that the description of the managerial competence of the Principals of Elementary Schools of Cluster III in Makassar Subdistrict of Makassar City shows that the competence of schools’ principals is in good category based on three aspects, namely planning, implementation, and evaluation. The effectiveness of the Principals’ Managerial Competence on Teachers’ Performance shows that the principals’ managerial skills has been conducted or it is categorized as good, especially in terms of cooperation and achieving educational goals.